On my honor - Bauer, Marion Dane. (New York Yearling, 1986)
When his best friend drowns while they are both swimming in a treacherous river that they had promised never to go near, Joel is devastated and terrified at having to tell both sets of parents the terrible consequences of their disobedience.
Keywords: Obedience -- Fiction; Accidents -- Fiction; Friendship -- Fiction; Conduct of life -- Fiction